ANALOGY AND HARMONY: AN ANALYSIS OF THE RIGHTS AND OBLIGATIONS OF ADOPTED CHILDREN IN THE DISTRIBUTION OF INHERITANCE FROM THE PERSPECTIVE OF ISLAM AND CHRISTIANITY - Alfida, Laila; Azhari, Aidul Fitriciada (istinbath, 2024)
This study examines an important comparative legal and religious issue regarding the rights of adopted children in inheritance distribution from Islamic and Christian perspectives. While the abstract summarises key findings, there is a risk of oversimplifying the complexities of religious doctrines and national legal systems governing inheritance laws. Although adopted children's rights are limited in Islamic law, the possibility of making a will can mitigate these restrictions; however, additional nuances arise from various schools of thought and interpretations that influence the scope of inheritance. Conversely, the Christian perspective is often generalised as uniformly granting equal rights to adopted children, which may only hold across some Christian denominations or legal systems influenced by Christian principles. The abstract would benefit from a more detailed analysis of internal variations within each religion and consideration of how different national laws operationalise religious principles. Furthermore, the notion of "harmony" between these two religious traditions in addressing justice for adopted children may be overstated, as the theological foundations guiding inheritance distribution differ fundamentally. A more critical engagement with potential conflicts or limitations in achieving harmonious legal frameworks would add depth to the analysis.